Thermal inertia assessment of an experimental extensive green roof in summer conditions. (March 2018) - Bevilacqua, Piero; Mazzeo, Domenico; Arcuri, Natale
Abstract: Passive solutions for building envelopes such as green roofs are regarded as promising tools to reduce the energy demand for buildings air-conditioning and to improve the thermal comfort of indoor spaces. It is therefore necessary to quantify and assess properly the summer thermal performance and to determine how a green roof cover can attenuate and delay the temperature and heat flux acting on its surface. The paper deals with an experimental investigation of the dynamic thermal characteristics of a vegetated roof situated on a university building roof in south Italy. An analysis of the daily values of dynamic parameters showed a quite stable trend of the decrement factor with variation in the range 0.0982–0.1920. The time lag exhibited a trend ranging from 7.2 h to 8.5 h. A successive analysis was developed decomposing the trends of temperature into Fourier series to assess the response of the vegetated systems to solicitations of different frequencies and to assess the deviations, in the calculation of the dynamic parameters, arising from considering a sinusoidal variation with a 24 h period of the external forcing, in accordance with the International Standard EN ISO 13786, compared to the experimental values. The green roofs showed a behaviour similar to a high-pass frequency system, and relative errors, by using only the fundamental harmonic under 10% were found for 72.9% of the cases for the decrement factor and for 93.8% of the data for the time lag. Results demonstrated that when climatic conditions of the location are more irregular then the predictions of the dynamic parameters considering only the fundament harmonic instead of the real trend of the forcing can provide more relevant errors.